Dual‐Responsive Nanocomposites for Synergistic Antibacterial Therapies Facilitating Bacteria‐Infected Wound Healing. Issue 6 (27th November 2022) - Cheng, Shi; Qi, Manlin; Li, Wen; Sun, Wenyue; Li, Meiqi; Lin, Jinying; Bai, Xue; Sun, Yue; Dong, Biao; Wang, Lin
Abstract: The rising dangers of bacterial infections have created an urgent need for the development of a new generation of antibacterial technologies and therapeutics. Antibacterial photodynamic therapy (PDT), considered as a noninvasive treatment with no drug resistance, has become a new promising photochemistry‐involved treatment strategy. Titanium oxide (TiO2 ) is proved to be a very efficient PDT agent among the photosensitive materials, while the property of a large bandgap of TiO2 makes it only be excited by ultraviolet light, which is harmful to organisms. In this work, a novel ligand‐to‐metal charge transfer (LMCT) mediated TiO2 PDT strategy is proposed via the harmless near‐infrared light irradiation. By choosing a mussel‐inspired material, polydopamine (PDA) is involved in forming mesoporous TiO2 @PDA nanoparticles (mTiO2 @PDA NPs). The catechol groups of PDA can attach the TiO2 tightly even in colloidal environments, and can also form the LMCT bridge, exciting TiO2 to exert PDT function via 808 nm irradiation. Combining the sonodynamic therapy (SDT) of TiO2 and the photothermal therapy properties of PDA, this simple structure mTiO2 @PDA enables synergistic antibacterial applications with multiple functions under the dual excitation of NIR and ultrasound. This reliable all‐in‐one NPs can achieve great antibacterial effect and a rapid repair of infected wounds. Abstract : This work here gives a ligand‐to‐metal charge transfer mediated mTiO2 @PDA nanoparticle that can be directly excited by NIR to achieve photodynamic therapy (PDT) effect. Triggered by NIR and ultrasound, mTiO2 @PDA can promote infected wound healing by PDT/PTT/SDT synergetic therapy. The mechanism of sterilization is the inhibition of physiological activities of bacteria, such as ribosome related functions, energy metabolism, and carbohydrate metabolism.